2015
DOI: 10.1371/journal.pntd.0003541
|View full text |Cite
|
Sign up to set email alerts
|

Low-level Laser Therapy to the Mouse Femur Enhances the Fungicidal Response of Neutrophils against Paracoccidioides brasiliensis

Abstract: Neutrophils (PMN) play a central role in host defense against the neglected fungal infection paracoccidioidomycosis (PCM), which is caused by the dimorphic fungus Paracoccidioides brasiliensis (Pb). PCM is of major importance, especially in Latin America, and its treatment relies on the use of antifungal drugs. However, the course of treatment is lengthy, leading to side effects and even development of fungal resistance. The goal of the study was to use low-level laser therapy (LLLT) to stimulate PMN to fight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Nevertheless, we believe that although LLLT can reduce the influx of PMN into a given site of inflammation, somewhat paradoxically, LLLT may also be able to increase the individual activity levels of those PMN. In a recent study we were able to demonstrate that even though irradiated PMN were present in lower numbers, they were far more active against virulent forms of Paracoccidioides brasiliensis (Pb), which is the fungus responsible for a neglected tropical disease known as paracoccidioidomycosis (PCM) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we believe that although LLLT can reduce the influx of PMN into a given site of inflammation, somewhat paradoxically, LLLT may also be able to increase the individual activity levels of those PMN. In a recent study we were able to demonstrate that even though irradiated PMN were present in lower numbers, they were far more active against virulent forms of Paracoccidioides brasiliensis (Pb), which is the fungus responsible for a neglected tropical disease known as paracoccidioidomycosis (PCM) .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously studied the effects of LLLT upon the behavior of PMN acting against an important fungal infection ( Paracoccidioides brasiliensis ), and observed that LLLT induced lesser PMN migration to the infection site; however, the PMN that did reach the site of infection were significantly more activated towards the fungal cells and could efficiently kill the microorganism due to higher PMN viability, and greater production of ROS as well as pro‐inflammatory proteins .…”
Section: Introductionmentioning
confidence: 99%
“…Studies with an arthritis model , and fungal disease model have found that laser therapy can improve the chemotaxis of neutrophils. However, the results in the literature on diabetic models are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…PBM is believed to promote angiogenesis, enhance neovascularization, increase collagen synthesis, and accelerate the healing of skin wounds . Recent studies have found that PBM at different wavelengths can modulate neutrophil chemotaxis and the cellular activation status of macrophages in inflammation processes .…”
Section: Introductionmentioning
confidence: 99%
“…Three other routes can also be mentioned, intravenous [ 23 ], intraoral [ 24 ], and intratracheal [ 25 ], and were not included in the present investigation. Nevertheless, the subcutaneous air-pouch technique that had already been shown to raise an almost pure pool of PMN, also being a local and controlled Pb infection [ 18 , 26 ], was now compared to other classical methods and did present the highest numbers of mature PMN in marrow, as well as recruited PMN in loco . Intraperitoneal injection of Pb , on the other hand, leads to an exsudate composed of 40–50% PMN [ 27 ].…”
Section: Discussionmentioning
confidence: 99%